A Seeding Reaction Recapitulates Intracellular Formation of Sarkosyl-insoluble Transactivation Response Element (TAR) DNA-binding Protein-43 Inclusions - Furukawa, Yoshiaki (American Society for Biochemistry and Molecular Biology, 2011)
The transactivation response element (TAR) DNA-binding protein-43 (TDP-43) is a nuclear protein that normally regulates transcription and splicing. Abnormal accumulation of insoluble inclusions containing TDP-43 has been recently reported in the affected tissues of amyotrophic lateral sclerosis (ALS) patients. Here, we show that intracellular aggregation of TDP-43 can be triggered by transduction of fibrillar aggregates prepared from in vitro functional TDP-43. Sarkosyl is found to be incapable of solubilizing those intracellularly seeded aggregates of TDP-43, which is consistent with the observation that TDP-43 inclusions in ALS patients are sarkosyl-insoluble. In addition, intracellular seeding in our cell models reproduces ubiquitination of TDP-43 aggregates, which is another prominent feature of TDP-43 inclusions in ALS patients. Although it has been so far difficult to initiate disease-associated changes of TDP-43 using cultured cell models, we propose that a seeding reaction is a key to construct a model to monitor TDP-43 pathologies.